Long non-coding RNA LINC00926 is a biomarker for naïve B-cells with prognostic value in advanced stage classic Hodgkin Lymphoma - Ingram Iaccarino; Thomas Beder; Sarah Reinke; Peter Borchmann; Bastian von Tresckow; Michael Altenbuchinger; Wolfram Klapper (Haematologica)
Not available.